Prevalence and Characteristics of mcr-1-Producing Escherichia coli in Three Kinds of Poultry in Changsha, China - Hu, Jufang; Yang, Jie; Chen, Wenxin; Liu, Zhihong; Zhao, Qin; Yang, Hui; Sun, Zhiliang; Chen, Xiaojun; Li, Jiyun (Frontiers in Microbiology, 2022)
Colistin is one of the last-line drugs against difficult to treat and multidrug-resistant Gram-negative bacteria. The emergence of mobile colistin resistance gene mcr-1 increased worldwide attention on colistin resistance. mcr-1 is the dominant gene that caused resistance to colistin in chicken-derived Escherichia coli (E. coli) in China; it has a broad resistance spectrum and causes multiple drug resistance problems. There are only few studies on mcr-positive E. coli (MCRPEC) from laying ducks and quails in China. Here, the molecular and epidemiological characteristics of MCRPEC from three kinds of poultry farms (laying duck, quail, and broiler) were investigated in Changsha, China. A total of 17 mcr-positive E. coli (MCRPEC) strains were screened in 690 samples from the three kinds of poultry farms. This is the first report on MCRPEC, to our best knowledge, derived from quail. All the MCRPEC strains were resistant to colistin, sulfamethoxazole-trimethoprim, florfenicol, tetracycline, and ciprofloxacin, and mildly resistant to tigecycline, gentamicin, piperacillin/tazobactam, cefotaxime, and ceftiofur. All the strains were sensitive to meropenem and amikacin. By bioinformatics analysis, 17 MCRPEC strains belonging to 11 MLST types were distributed in phylogroups A (58.8%), B1 (23.5%), and phylogroup D (17.6%). mcr-1 was located in IncI2 plasmid with typical plasmid conjugation transfer part, type IV secretory system, and tellurium-resistant protein, increasing transmission capacity to other bacteria. Monitoring of colistin-resistant bacteria in poultry farms should be strengthened.